MODERN APPROACHES TO THE CONTENT OF THE CONCEPT INTEGRATED RISK MANAGEMENT SYSTEM IN BANKS - D. E. Alisheva; A. M. Nurgaliyeva (Academic Journal of Physical and Chemical Sciences, 2019)
The integrated risk management system involves the adoption of strategic decisions that will contribute to the achievement of the Bank’s overall corporate goals. In other words, the risk management system should be integrated into the overall strategy of the Bank. Moreover, the integrated risk management system should be based on continuous monitoring of potential risks at each level of the management system. This article analyzes the main stages of risk management development and various approaches that reveal the essence of integrated risk management in banks.